Mathematical Literacy Assessment: A Scalable Mobile Adaptive Blueprint for Mapping Proficiency Across PISA Domains - Falani Falani; Syamsir Sainuddin (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2026)
Indonesian students continue to struggle with mathematical literacy, as demonstrated across several cycles of PISA assessments. This study addresses this gap by applying a Rasch-based diagnostic approach to map patterns of item difficulty and examine how students across different grade levels engage with key indicators and content domains. A total of 271 students in Grades VII to IX from Indonesian public schools completed a 32-item multiple-choice test aligned with the PISA indicators of Formulating, Employing, Interpreting, and Reasoning. The instrument was specifically designed to capture different cognitive levels and situational contexts within the mathematical literacy framework. Rasch analysis was used to evaluate person ability, item difficulty, model fit, and measurement assumptions. The model showed strong empirical evidence, with a person reliability of 0.85, item reliability of 0.98, and infit/outfit MNSQ values within the acceptable range (0.5 to 1.5), and no significant Differential Item Functioning was found across grade levels. Formulating was the most difficult indicator, while Interpreting was the easiest. Among the content domains, Space and Shape posed the greatest challenge, whereas Quantity was the most accessible domain. Grade VIII students demonstrated the highest mean ability, producing a non-linear pattern across grade levels, likely due to a shift in Grade IX toward procedural exam-oriented instruction that narrows the focus on high-order modeling skills. Findings suggest that difficulties in modelling and spatial reasoning arise from deeper conceptual issues rather than grade progression alone. These results highlight the need for instructional practices that place greater emphasis on modelling processes and spatial reasoning.